Through and through : Toledo stories - Geha, Joseph (Arab American writing., 2009)
Treasured in the Arab-American literary community, Through and Through is a collection of broadly interrelated stories, eight originally published in 1990 with three new stories added in the second edition. One of the first books of modern Arab-American fiction, Joseph Geha's stories offer a warm, inspired portrait of an extended Arab family in a Lebanese and Syrian community in Toledo, Ohio, spanning the decades between the 1930s and the present. In a series of vignettes, Geha follows three generations of an Arab-American family as they create a new community and way of life, struggling to keep their Arab roots vital while adapting their culture to new conditions. In "Holy Toledo" Nadia, "a tomboy in her dungarees" watches American women come into her town to shop. Although she calls them silly, she "wished that she were one of them, returning with them into that huge strangeness, America, luring her despite the threat it seemed to hold of loss and vicious homesickness." Portraying both the anguish and the humor of negotiating between the old world and the new, these stories offer a passionate, unvarnished glimpse into the lives of an immigrant community."